Rancang Bangun Sistem Informasi Perkembangan Ternak pada Dinas Peternakan Kabupaten Toli-Toli - Zulkarnain, Zulkarnain; Bakri, Bakri (Fakultas Teknik, Universitas Tadulako, 2020)
This study aims to: (1) design livestock development information systems in the Tolitoli Regency Livestock Services, (2) test and implements livestock development information systems in the Tolitoli Regency Livestock Services, (3) find out the extent of speed and accuracy in processing data with the system manuals and computerized systems at the Tolitoli Regency Livestock Services. The study was conducted at the Animal Husbandry Office of Tolitoli Regency located on Hi street. Mallu No.11 Tolitoli. The data used in this study are secondary data and primary data through direct observation, interviews and literature studies. The system design method uses waterfall and the testing system uses a black box. The results of this study are in the form of livestock development information systems in the Tolitoli Regency Livestock Services, which can facilitate the Tolitoli Regency Livestock Services especially in the field of livestock development in data processing and reporting. This information system provides a service (feature): processing data on farmer groups and livestock development. This information system was built using the Java programming language with the editor (IDE) Netbeans 8, JDK 7, making reports with Jaspersoft iReport and the MySQL database